2010
DOI: 10.1177/0146167209359768
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Theories of Body Weight: Entity Beliefs Can Weigh You Down

Abstract: The current research extended the implicit theory approach to a weight management context and merged it with value expectancy theory. Three studies investigated the hypothesis that individuals are especially unlikely to self-regulate effectively after dieting setbacks when they believe body weight to be fixed (entity theory) rather than malleable (incremental theory). Study 1 examined avoidant coping after a hypothetical dieting setback. Study 2 examined the implicit theory-avoidant coping relation after natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
188
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(193 citation statements)
references
References 55 publications
4
188
1
Order By: Relevance
“…Though we do not disagree with this finding, we propose that people have other lay theories about the 473121P SSXXX10.1177/0956797612473121McFerran, MukhopadhyayLay Theories of Obesity research-article2013 causes of obesity that are more prevalent than theories involving genes or social networks. Individuals' food and exercise choices are influenced by the lay theories they hold (Burnette, 2010;Crum & Langer, 2007), and the stigma of obesity is rooted in the belief that individuals are largely responsible for their weights (Crandall, 1994;Puhl & Brownell, 2001). Indeed, people can make vast and relatively rapid changes to their diet and exercise patterns, but not to their genes or social networks.…”
Section: Research Articlementioning
confidence: 99%
“…Though we do not disagree with this finding, we propose that people have other lay theories about the 473121P SSXXX10.1177/0956797612473121McFerran, MukhopadhyayLay Theories of Obesity research-article2013 causes of obesity that are more prevalent than theories involving genes or social networks. Individuals' food and exercise choices are influenced by the lay theories they hold (Burnette, 2010;Crum & Langer, 2007), and the stigma of obesity is rooted in the belief that individuals are largely responsible for their weights (Crandall, 1994;Puhl & Brownell, 2001). Indeed, people can make vast and relatively rapid changes to their diet and exercise patterns, but not to their genes or social networks.…”
Section: Research Articlementioning
confidence: 99%
“…Why do some dieters feel confident in their ability to face challenges to their weight-loss goals, whereas others feel they lack the requisite skills? Research on implicit theories has sought to answer these and similar questions for decades, examining how lay beliefs, namely incremental theories (beliefs that human attributes can be improved or developed) and entity theories (beliefs that human attributes are fixed or invariant), influence self-regulation (Dweck & Leggett, 1988;Molden & Dweck, 2006).Although research on implicit theories originated within an academic context, scholars have extended the theory to additional achievement domains, such as athletics (e.g., Kasimatis, Miller, & Marcussen, 1996;Ommundsen, 2003), weight management (Burnette, 2010), and leadership (Burnette, Pollack, & Hoyt, 2010). Across these contexts, implicit theories have been postulated to be linked to various self-regulatory processes, including goal setting (e.g., Robins & Pals, 2002), social comparison (Nussbaum & Dweck, 2008), overcoming stereotype threat (e.g., Aronson, Fried, & Good, 2002), selective information attention (Mangels, Butterfield, Lamb, Good, & Dweck, 2006), and remedial action (e.g., Hong, Chiu, Dweck, Lin, & Wan, 1999).…”
mentioning
confidence: 99%
“…In addition, although differences in implicit theories are often conceptualized at a dispositional level (see Dweck, 2009), these theories, like other schemas and beliefs, exhibit some degree of day-today and moment-to-moment fluctuation (e.g., Franiuk, Pomerantz, & Cohen, 2004). Indeed many scholars have primed implicit theories (e.g., Burnette, 2010;Hong et al, 1999), and temporarily changed them in both one-shot laboratory experiments (e.g., Spray, Wang, Biddle, Chatzisarantis, & Warburton, 2006) and longer-term interventions (e.g., Blackwell, Trzesniewski, & Dweck, 2007;Burnette & Finkel, 2012).Regardless of achievement context or methodological approach, implicit theories are hypothesized to be related to an array of self-regulatory processes (e.g., Molden & Dweck, 2006). Namely, it is hypothesized that incremental theorists set goals focused on learning, employ mastery-oriented strategies to reach these goals, and report greater confidence and expectations when evaluating the potential for goal success.…”
mentioning
confidence: 99%
“…In this line of thinking, there are other studies that have found similar results. For example, it has been suggested that individuals' food and exercise choices may be influenced by the beliefs that people have (Burnette, 2010). This author found that individuals were especially unlikely to self-regulate effectively after dieting setbacks when they believed body weight must be fixed rather than malleable (Burnette, 2010).…”
Section: * Introductionmentioning
confidence: 99%
“…For example, it has been suggested that individuals' food and exercise choices may be influenced by the beliefs that people have (Burnette, 2010). This author found that individuals were especially unlikely to self-regulate effectively after dieting setbacks when they believed body weight must be fixed rather than malleable (Burnette, 2010). Additionally, it has been suggested that fostering the belief that body weight is changeable helps people to avoid setback related weight-gain (Burnette & Finkel, 2012).…”
Section: * Introductionmentioning
confidence: 99%